2019
DOI: 10.1371/journal.pone.0214634
|View full text |Cite
|
Sign up to set email alerts
|

Correction: The ArcAB two-component regulatory system promotes resistance to reactive oxygen species and systemic infection by Salmonella Typhimurium

Abstract: The contributions of this author are as follows: acquisition of data, analysis and interpretation of data, the development of methodology, and making a critical review. The correct citation is: Pardo-Esté C, Hidalgo AA, Aguirre C, Inostroza A, Briones AC, Cabezas CE, et al. (2018) The ArcAB two-component regulatory system promotes resistance to reactive oxygen species and systemic infection by Salmonella Typhimurium. PLoS ONE 13 (9): e0203497.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Many bacterial TCSs, have been involved in intracellular survival mechanisms in eukaryotic cells, such as EvgSA in Shigella flexneri [54]; ArcAB [55], PhoPQ [56] and EnvZ/OmpR [57] in Salmonella Thyphimurium; SrrAB [58]; GraSR [59] in Staphylococcus aureus; PhoPQ in Escherichia coli [60]; BvrSR in Brucella abortus [61]; and PrrAB in Mycobacterium tuberculosis [62], among others. In S. pneumoniae, most of the TCSs are required for full virulence in animal models of infection [63,64] and we have shown that two of these systems, StkP/ComE and CiaRH [15,16], are important in response to acidic and/or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacterial TCSs, have been involved in intracellular survival mechanisms in eukaryotic cells, such as EvgSA in Shigella flexneri [54]; ArcAB [55], PhoPQ [56] and EnvZ/OmpR [57] in Salmonella Thyphimurium; SrrAB [58]; GraSR [59] in Staphylococcus aureus; PhoPQ in Escherichia coli [60]; BvrSR in Brucella abortus [61]; and PrrAB in Mycobacterium tuberculosis [62], among others. In S. pneumoniae, most of the TCSs are required for full virulence in animal models of infection [63,64] and we have shown that two of these systems, StkP/ComE and CiaRH [15,16], are important in response to acidic and/or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Many bacterial TCSs, have been involved in intracellular survival mechanisms in eukaryotic cells, such as EvgSA in Shigella flexneri [ 54 ]; ArcAB [ 55 ], PhoPQ [ 56 ] and EnvZ/OmpR [ 57 ] in Salmonella Thyphimurium; SrrAB [ 58 ]; GraSR [ 59 ] in Staphylococcus aureus ; PhoPQ in Escherichia coli [ 60 ]; BvrSR in Brucella abortus [ 61 ]; and PrrAB in Mycobacterium tuberculosis [ 62 ], among others. In S .…”
Section: Discussionmentioning
confidence: 99%
“…Many bacterial TCSs, have been involved in intracellular survival mechanisms in eukaryotic cells, such as EvgSA in Shigella flexneri [49]; ArcAB [50], PhoPQ [51] and EnvZ/OmpR [52] in Salmonella thyphimurium ; SrrAB [53]; GraSR [54] in Staphylococcus aureus ; PhoPQ in Escherichia coli [55]; BvrSR in Brucella abortus [56]; and PrrAB in Mycobacterium tuberculosis [57], among others. In S. pneumoniae , most of the TCSs are required for full virulence in animal models of infection [58, 59] and we have shown that two of these systems, StkP/ComE and CiaRH [15, 16], are important in response to acidic and/or oxidative stress.…”
Section: Discussionmentioning
confidence: 99%